The meaning of color in ancient Mesopotamia - Thavapalan, Shiyanthi, author.
1 online resource.
Keywords: In The Meaning of Color in Ancient Mesopotamia, Shiyanthi Thavapalan offers the first in-depth study of the words and expressions for colors in the Akkadian language (c. 2500-500 BCE). By combining philological analysis with the technical investigation of materials, she debunks the misconception that people in Mesopotamia had a limited sense of color and positions the development of Akkadian color language as a corollary of the history of materials and techniques in the ancient Near East.